Case study of brazilian electric matrix: choice of sources not emitters co2 assisted by AHP method - Brandão, Yago Fraga Ferreira; Vasconcelos, Wagner Eustáquio de; Sales , Ingrid Torres (Brazilian Journal of Production Engineering, 2022)
The Brazilian electricity matrix has hydroelectric plants as its main source of energy, where they represent about 67% of the electrical potential used to supply the country. Understanding that it is not feasible to have the electrical system dependent on this single source, this work analyzes the applicability of energies: Wind, Solar, and Nuclear in the electric supply of the Brazilian territory, allied to the study of decision making to make the matrix more balanced and less dependent on a single energy source. Criteria (availability of resources; financial costs; biosafety and climatology) and alternatives (wind, solar and nuclear energy) were chosen. After the definition, the importance of each criterion was judged using the Saaty table, generating the judgment matrix. After generating the matrix, the coherence ratio was checked, which was 1.16% (within the limit). Five scenarios were defined (northeast, Midwest, north, south, and southeast regions) and percentages were established for each criterion. The results of the percentages for each criterion were gathered in the five scenarios and with the help of an algorithm developed in MATLAB, the simulation was performed using the AHP method (Analytic Hierarchy Process). The results showed that, for the criteria and scenarios adopted, four Brazilian regions presented feasibility for at least two energy sources, with the northeast region being viable for all alternatives adopted. It is expected that from the results found, future works will be generated that discuss the issue of national electrical imbalance, approaching new criteria, energies, and decision-making methods.